Shared care versus hospital-based cardiac rehabilitation: a cost-utility analysis based on a randomised controlled trial. Issue 1 (7th February 2018) - Bertelsen, Jannik B; Dehbarez, Nasrin Tayyari; Refsgaard, Jens; Kanstrup, Helle; Johnsen, Søren P; Qvist, Ina; Christensen, Bo; Søgaard, Rikke; Christensen, Kent L
Abstract : Background: Changes in the organisation of chronic healthcare, an increased awareness of costs and challenges of low adherence in cardiac rehabilitation (CR) call for the exploration of more flexible CR programmes as alternatives to hospital-based CR (H-CR). A model of shared care cardiac rehabilitation (SC-CR) that included general practitioners and the municipality was developed. The aim of this study was to analyse the cost utility of SC-CR versus H-CR. Methods: The cost-utility analysis was based on a randomised controlled trial of 212 patients who were allocated to SC-CR or H-CR and followed up for 12 months. A societal cost perspective was applied that included the cost of intervention, informal time, healthcare and productivity loss. Costing was based on a microcosting approach for the intervention and on national administrative registries for the other cost categories. Quality-adjusted life years (QALYs) were based on the EuroQol 5-Dimensions measurements at baseline, after 4 months and after 12 months. Conventional cost-effectiveness methodology was employed to estimate the net benefit of SC-CR. Results: The average cost of SC-CR was 165.5 kDKK and H-CR 163 kDKK. Productivity loss comprised 74.1kDKK and 65.9 kDKK. SC-CR cost was an additional 2.5 kDKK (95% CI −38.1 to 43.1) ≈ (0.33; −5.1 to 5.8 k€) and a QALY gain of 0.02 (95% CI −0.03 to 0.06). The probability that SC-CR would be cost-effective was 59% for a threshold value of willingness to pay of 300 kDKK (k€40.3). Conclusion: CR after shared care model and H-CR are comparable and similar in socioeconomic terms. Trial registration number: NCT 01522001; Results.